Analysis of Government Expenditures, Private Investment and Gross Regional Domestic Products on Absorption of Labor in Kalimantan - BUBI BUBI; WIWIN ZAKIAH; KARMEN MARPAUNG (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
ABSTRACT The purpose of this study was to determine the influence of government expenditures, private investment, and Gross Regional Domestic Products, on absorption of labor in Kalimantan. This research is in the form of descriptive analysis using secondary data in the form of panel data from 2005-2016 obtained from the Central Bureau of Statistics with data consisting of government expenditures, private investment, GRDP, and absorption of labor. Furthermore, the data were analyzed using the Multiple Linear Regression analysis method. The results showed that government expenditure did not significantly influence employment, private investment has a positive and significant influence on employment, GRDP has a significant and positive influence on employment. Then simultaneously government expenditure, private investment, and GRDP have a positive and significant influence on employment.